Effect of Mind Mapping as a Learning Tool on Online Learning of Chemistry - GEORGE NYAGBLORMASE; ALEXANDER GYAMPOH; James Hinson; BENJAMIN AIDOO; Ernest Yeboah (Studies in Learning and Teaching, 2021)
The advent of the Covid-19 pandemic brought distortions in the academic calendar of nations when educational institutions were closed. As a way of filling the gap created in the trend, tertiary institutions introduced online learning to support students’ learning while at home. There was also the need to introduce alternative learning approaches to students that will help them summarize and represent the lengthy lecture notes and reading materials into meaningful and memorable units. This study looks at the effectiveness of mind maps in promoting this home-based online learning. The participants were seventy-one (71) first-year Bachelor of Education students pursuing a 4-year degree program in Basic Education in Kibi Presbyterian College of Education. One group consists of students pursuing Home Economics as their major and the other primary education. A test and questionnaire were used to collect data. T-test was used to test the significance of the performance of the two groups, and multiple regression was used to find an association between the use of the strategy and students’ performance. The statistical software used for data analysis was IBM’s SPSS version 25. The result shows that the mind map strategy helped learners retain knowledge; however, students’ understanding of concepts was low